ABCA7 p.G215S as potential protective factor for Alzheimer’s disease - Sassi, C.; Nalls, M.A.; Ridge, P.G.; Gibbs, R.; Ding, J.; Lupton, M.K.; Troakes, C.; Lunnon, K.; Al-Sarraj, S.; Brown, K.S.; Medway, C.; Clement, Naomi; et al. (Elsevier, 2016)
Genome-wide association studies (GWASs) have been effective approaches to dissect common genetic variability underlying complex diseases in a systematic and unbiased way. Recently, GWASs have led to the discovery of over 20 susceptibility loci for Alzheimer’s disease (AD). Despite the evidence showing the contribution of these loci to AD pathogenesis, their genetic architecture has not been extensively investigated, leaving the possibility that low frequency and rare coding variants may also occur and contribute to the risk of disease. We have used exome and genome sequencing data to analyse the single independent and joint effect of rare and low frequency protein coding variants in 9 AD GWAS loci with the strongest effect sizes after APOE (BIN1, CLU, CR1, PICALM, MS4A6A, ABCA7, EPHA1, CD33, CD2AP) in a cohort of 332 sporadic AD cases and 676 elderly controls of British and North American ancestry. We identified coding variability in ABCA7 as contributing to AD risk. This locus harbors a low frequency coding variant (p.G215S, rs72973581, MAF=4.3%) conferring a modest but statistically significant protection against AD (p-value= 6x10-4, OR=0.57, 95% CI 0.41-0.80). Notably, our results are not driven by an enrichment of loss of function variants in ABCA7, recently reported as main pathogenic factor underlying AD risk at this locus. In summary, our study confirms the role of ABCA7 in AD and provide new insights that should address functional studies.